2007
DOI: 10.1097/01.hp.0000278842.39156.93
|View full text |Cite
|
Sign up to set email alerts
|

Physical Dosimetry of Chernobyl Cleanup Workers

Abstract: This paper presents a critical review of dosimetric monitoring practices during Chernobyl cleanup from 1986 to 1990. Dosimetric monitoring is considered in time evolution with respect to legislative background (including dose limits), methods of dose assessment, and coverage of workers with radiation monitoring programs as well as availability of data on individual doses of liquidators. Four large independent dosimetry services (Administration of Construction No. 605, Chernobyl Nuclear Power Plant, Production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…Reconstruction of individual doses due to external gamma-irradiation for the subjects of Ukrainian-American Chornobyl Ocular Study (UACOS) (Worgul et al 2007) was based on retrospective assessment of reliability and possible bias of ODRs and their recalibration against EPR dosimetry with tooth enamel in this case (Chumak et al 2007). Results suggested that ODRs of military liquidators overestimate EPR doses by a factor of 2.2, and that ODRs should be adjusted (recalibrated) prior to use in risk analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reconstruction of individual doses due to external gamma-irradiation for the subjects of Ukrainian-American Chornobyl Ocular Study (UACOS) (Worgul et al 2007) was based on retrospective assessment of reliability and possible bias of ODRs and their recalibration against EPR dosimetry with tooth enamel in this case (Chumak et al 2007). Results suggested that ODRs of military liquidators overestimate EPR doses by a factor of 2.2, and that ODRs should be adjusted (recalibrated) prior to use in risk analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The reliability and validity of the official doses depend on the time period considered and the type of work performed (Ilyin 1995; Chumak 2007; Bouville and Kryuchkov 2014). Reviews of official doses have revealed their possible bias and low accuracy, to degrees strongly correlated with the affiliation of the cleanup worker and, therefore, the type of dosimetric monitoring received at the time of cleanup (Chumak 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described elsewhere,1 22 23 the cleanup workers were dominantly exposed to γ-radiation released mainly by 131 I, 134 Cs and 137 Cs. Received radiation doses were measured by individual or group dosimeters, or estimated by work area measurements.…”
Section: Methodsmentioning
confidence: 99%
“…gamma and x-rays) doses that depended primarily on their work locations and on the time after the accident when the work was performed. Unfortunately, for a number of reasons, individual doses were monitored inadequately or were not monitored at all for the majority of liquidators (Chumak 2007). There were also problems with the registration and archival of the results of dosimetric monitoring.…”
Section: Introductionmentioning
confidence: 99%